PENGARUH KEPEMIMPINAN, KOMPENSASI, MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Kasus pada KaryawanPT.Indomarco Prismatama Cabang Malang) - Desi Nurdiana; Muhammad Mansur; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThe purpose of this study to determine the influence of Leadership, Compensation, Motivation and Organizational Commitment to Employee Performance. Data analysis method used in this research is Multiple Linear Regression Analysis.Based on the results of this study that positive and significant Leadership on Employee Performance this is evidenced from the value of variable coefficient of 1.987 and a significant value of 0.050. Compensation has a positive and significant impact on Employee Performance, this is evidenced from the value of variable coefficient of 2.594 and significant value of 0.011. Motivation has a positive and significant impact on Employee Performance, this is evidenced from the value of the variable coefficient of 4.422 and a significant value of 0.000. Organizational Commitment positive and insignificant to Employee Performance, this is evidenced from the value of variable coefficient of 0.256 and significant value of 0.799. As well as the significant value of Fuji 0,000 <0.05, where H04 is accepted, which means there are some free variables that have the ability to explain the dependent variable (Employee Performance).Keywords: Leadership, Compensation, Motivation and Organizational Commitment Employee Performance